Exploring block and permeation of N-methyl-D-Aspartate (NMDA) receptor channels for treatment of neurodegenerative disorders - Abu, Izuddin Fahmy (2016)
N-methyl-D-aspartate receptors (NMDAR) are ionotropic glutamate receptors which can be blocked by Mg2+ in a voltage-dependent manner and are highly permeable to Ca2+, hence they represent a medically relevant target for neurodegenerative disorders caused by excitotoxicity. The two main objectives of this study were, (i) to determine the impact of Q/R/N, +1 and -8 sites modification in the M2 pore region of GluN2A NMDAR subunit on Mg2+ block and other open channel blockers; and (ii) to evaluate novel multi-target-directed ligands (MTDL) for Alzheimer’s disease therapy. The Xenopus laevis oocyte expression system was employed where NMDAR subunit cRNAs were injected into the oocytes and responses to NMDA/glycine and channel blockers were recorded using two-electrode voltage clamp (TEVC) electrophysiology.